Post a New Question


posted by .

Let y = u^3+6u, where u = 2x^4+3x^2-2
Find dy/dx.


2) Let f(x) = 1/sqrt(4x^2-x). Determine f'(x).

3) Let y = 5/cubrt((2x-5)^2). Determine dy/dx.

  • Calculus -

    1) dy/dx = dy/du*du/dx
    = (3 u^2 + 6)(8x^3 + 6x)
    To get it in terms of x only, substitute the u(x) function for u.

    2) Use the same "function of a function" approach as above. Let
    u = 4x^2 -x
    f(u) = u^(-1/2)
    df/dx = df/du*du/dx

    3) Let u = (2x-5)
    f(u) = 5/u^(2/3)
    Use the same procedure

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question